2022
DOI: 10.31083/j.fbl2709275
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-22-3p from Mesenchymal Stem Cells Inhibits the Epithelial-Mesenchymal Transition (EMT) of Melanoma Cells by Regulating LGALS1

Abstract: Background:The mortality rate from melanoma has been rising and hence new therapeutic approaches for this disease have received extensive attention, especially the search for novel therapeutic targets. The aim of this study was to find new targets for the treatment of melanoma through a bioinformatics and experimental approach. Methods: First, we screened for differentially expressed genes (DEGs) and differentially expressed miRNAs (DEMs) between melanoma and normal tissues using the TCGA-SKCM, GTEX, and GSE24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Methods for loading these cargoes include electroporation, sonication, co-incubation, and extrusion [ 136 , 137 , 138 , 139 , 140 , 141 ]. Endogenous loading involves the packaging of biomolecules via the modification of donor cells [ 133 , 134 , 142 , 143 , 144 , 145 ]. This modification of donor cells can be performed by means of the transfection of DNAs and various ncRNAs.…”
Section: Exosomes As Carriers Of Drug/sirnas/mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods for loading these cargoes include electroporation, sonication, co-incubation, and extrusion [ 136 , 137 , 138 , 139 , 140 , 141 ]. Endogenous loading involves the packaging of biomolecules via the modification of donor cells [ 133 , 134 , 142 , 143 , 144 , 145 ]. This modification of donor cells can be performed by means of the transfection of DNAs and various ncRNAs.…”
Section: Exosomes As Carriers Of Drug/sirnas/mirnasmentioning
confidence: 99%
“…Since exosomal miRNAs play important regulatory roles in cancer initiation and progression, it is reasonable to expect that modified exosomes carrying miRNAs could regulate cancer cell proliferation. BMSC-derived exosomes coated with miR-22-3p via transfection inhibit the proliferation of human melanoma cells by suppressing EMT and targeting galectin 1 (LGALS1) [ 142 ]. Hepatic stellate cell-derived exosomes that have been loaded with miR-335-5p via transfection suppress both the proliferation of hepatic cancer cells and in vivo tumor growth [ 143 ].…”
Section: Exosomes As Carriers Of Drug/sirnas/mirnasmentioning
confidence: 99%
“…In melanoma, epithelial-mesenchymal transition (EMT) is usually occurred when epithelial cells transit into mesenchymal cells, thereby promoting tumor metastasis and therapy resistance (28). Chen et al (39) demonstrated that MSC-EVs carried miR-22-3p could reduce the expression of EMT related gene LGALS1 in melanoma cells so as to inhibit the EMT process of tumor epithelial cells. However, this study is lack of animal studies, and the therapeutic potential of MSC-EVs with miR-22-3p needed further investigation, especially the clinical trials.…”
Section: Crosstalk Between Evs and Stromal Cells In Melanomamentioning
confidence: 99%
“…Studies have also confirmed that the down-regulation of miR-5100 can inhibit the metastasis of melanoma cells (MCs) [ 11 ]. Some studies used MCs (WM-266-4) as research material and the results suggested that the expression of miR-22-3p in the melanoma group was lower relative to the controls, and miR-22-3p suppressed the epithelial-mesenchymal transition (EMT) of MCs by regulating recombinant human galectin-1 (LGALS1) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%